Museums and Atlantic Slavery - Araujo, Ana Lucia (Milton, UNITED KINGDOM Routledge, 2021)
Museums and Atlantic Slavery explores how slavery, the Atlantic slave trade, and enslaved people are represented through words, visual images, artifacts, and audiovisual materials in museums in Europe and the Americas. Divided into four chapters, the book addresses four recurrent themes: wealth and luxury; victimhood and victimization; resistance and rebellion; and resilience and achievement. Considering the roles of various social actors who have contributed to the introduction of slavery in the museum in the last thirty years, the analysis draws on selected exhibitions, and institutions entirely dedicated to slavery, as well as national, community, plantation, and house museums in the United States, England, France, and Brazil. Engaging with literature from a range of disciplines, including history, anthropology, sociology, art history, tourism and museum studies, Araujo provides an overview of a topic that has not yet been adequately discussed and analysed within the museum studies field. Museums and Atlantic Slavery encourages scholars, students, and museum professionals to critically engage with representations of slavery in museums. The book will help readers to recognize how depictions of human bondage in museums and exhibitions often fail to challenge racism and white supremacy inherited from the period of slavery.
OCLC-licensed vendor bibliographic record.
Keywords: HISTORY / General; Slavery in museum exhibits; Slavery -- Historiography -- Social aspects; Slave trade -- Historiography -- Social aspects; Slave trade -- Museums